Evidence for Resilient Agriculture (ERA): graphical abstract - Rosenstock, Todd S.; Nowak, Andreea C.; Steward, Peter R.; Lamanna, Christine; Kamau, Hannah N. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Data on the performance of agricultural management practices and technologies was inaccessible and impractical. ERA compiled and organized it into a dynamic analytical engine that generates actionable, user-centered decision-making support